IL-6 and the dysregulation of immune, bone, muscle, and metabolic homeostasis during spaceflight. (December 2018) - Smith, John
Abstract We have previously reported that exercise-related secretion of IL-6 by peripheral blood mononuclear cells is proportionate to body weight, suggesting that IL-6 is gravisensitive and that suboptimal production of this key cytokine may contribute to homeostatic dysregulations that occur during spaceflight. This review details what is known about the role of this key cytokine in innate and adaptive immunity, hematopoiesis, and in bone, muscle and metabolic homeostasis on Earth and in the microgravity of space and suggests an experimental approach to confirm or disavow the role of IL-6 in space-related dysregulations.